To the 70th Anniversary of the Stavropol Research Anti-Plague Institute: Formation, Establishing, Operation, and Prospects of Development - A. N. Kulichenko; T. V. Taran; D. A. Kovalev; O. V. Maletskaya; S. A. Kurcheva; N. F. Vasilenko (Проблемы особо опасных инфекций)
.